PERANCANGAN SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS WEB DENGAN JAVA - Sandra Jamu Kuryanti (Jurnal Khatulistiwa Informatika, 2014)
Information and communication technology is currently growing rapidly. Internet is one of the information and communication technology that is currently very popular and liked by the public. Internet today many uses, among others, to seek information, promotion, and so forth. School academic information system is one of the web-based information system created in order to provide convenience especially to teachers in informing the data value to students. That way the data reporting process of the students can be informed quickly and accurately. Academic information system containing information about teacher data, the data value, the data subjects, and schedule data. Academic information system serves as the academic data processing so that the data can be used as academic academic information that will be presented to the faculty and students.Keyword: Internet, Academic Information, Web-based information system